Contextualizing the Insurance Industry Vigilance in Adopting PSAK 74 Through the Cosmology of “Yoga Kshema” - Resi Ariyasa Qadri; Yolanda Mayang Sari; Arifah Fibri Andriani; Rahayu Kusumawati (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2022)
This research aims to answer two main questions about the impacts of implementing PSAK 74 on the insurance industry in Indonesia, and the readiness of the industry to implement the latest insurance accounting standard. This study employed qualitative research inquiry using the video method. The data in this study were sourced majorly from the results of an onlineobservation in PSAK 74 webinars followed by documentation of relevant literature to synthesize knowledge on the implementation of PSAK 74 in Indonesia. Several interviews were conducted with academics and insurance practitioners to validate the knowledge. The collected data were analyzed by utilizing video-based analysis. This study concludes that the insurance sector in Indonesia has experienced a major obstacle related to the competence of accountants during the preparation of the PSAK 74 implementation. In addition, a significant overhaul of the company’s accounting information system is necessary to meet all the PSAK 74 requirements. This research contributes to providing insightful knowledge for the Indonesian insurance industry regarding crucial changes in the company’s financial reporting system as a result of the PSAK 74 implementation.